Fikcje krytycznoliterackie. Polemika Wacława Borowego i Manfreda Kridla - Gorczyński, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The paper The Fictions of Literary Criticism refers to a polemic between Manfred Kridl and Waclaw Borowy which was conducted in several articles published in the years 1936–1957. The polemic played a significant role in the development of modern Polish literary criticism. The matter of dispute was a new method of literary criticism announced by Kridl in his renowned Introduction to the Research of Literary Work (1936). The main topics of the discussion were the problems of the literary process, the evaluation of a literary work and the uses of scientific methods in humanities. The paper’s author pays attention especially to the rhetorical and literary means of argumentation which were used in the creation of this unusual form of non-fiction.